Necesidades del cuidador informal asociado al cuidado del adulto mayor dependiente. Centro de salud Monteverde. Santa Elena. Periodo. enero - abril 2023 - Blanca Piedad Llumitaxi Chimbo, (2024)
Informal caregivers of dependent older adults play a crucial role in the care of this age group, developing multiple activities that drastically affect their quality of life and generate biopsychosocial needs. Objective: To identify the needs of the informal caregiver associated with the care of dependent older adults. Methodology: A quantitative, descriptive, correlational and cross-sectional study was carried out in a population of 33 informal caregivers who are part of the Club for older adults of the Monteverde Health Center, Santa Elena. Two instruments were applied: Survey "Needs of the informal caregiver" with a Cronbach's Alpha reliability of 0.8207 and the Barthel Indicator tool" with an internal reliability of 0.98. Results: There was a predominance of informal caregivers of female gender (97%); of intermediate adult age (82%), with basic education levels (61%), unemployed (58%) and with a degree of kinship of family type (100%). It was identified that (93%) of informal caregivers present a deterioration in their state of health after initiating the caregiving functions, resulting in the presence of physical, psychological, time, social, safety, security, help, economic, training and information needs, with lesser intensity of parental and affection needs; For the correlation of variables, the chi-square test was used, obtaining a p- value = .004, which indicates that the needs of the informal caregiver are dependent on the care of the dependent older adult. Conclusion: there is an association between the needs of the informal caregiver and the care of the dependent older adult. Keywords: dependent older adults, quality, informal caregivers, biopsychosocial needs